2021
DOI: 10.3389/fcimb.2021.701278
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infects Endothelial Cells In Vivo and In Vitro

Abstract: SARS-CoV-2 infection can cause fatal inflammatory lung pathology, including thrombosis and increased pulmonary vascular permeability leading to edema and hemorrhage. In addition to the lung, cytokine storm-induced inflammatory cascade also affects other organs. SARS-CoV-2 infection-related vascular inflammation is characterized by endotheliopathy in the lung and other organs. Whether SARS-CoV-2 causes endotheliopathy by directly infecting endothelial cells is not known and is the focus of the present study. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 55 publications
7
105
0
Order By: Relevance
“…In addition, SARS-CoV-2 was detected in pulmonary endothelial cells by electron microscopy in critically ill patients with COVID-19 [ 119 ]. Furthermore, SARS-CoV-2 successfully infected engineered human blood vessel organoids and activated mature mouse aortic endothelial cells [ 120 , 121 ]. These findings support SARS-CoV-2 tropism for vascular endothelial cells.…”
Section: Endothelial Dysfunction In Covid-19mentioning
confidence: 99%
“…In addition, SARS-CoV-2 was detected in pulmonary endothelial cells by electron microscopy in critically ill patients with COVID-19 [ 119 ]. Furthermore, SARS-CoV-2 successfully infected engineered human blood vessel organoids and activated mature mouse aortic endothelial cells [ 120 , 121 ]. These findings support SARS-CoV-2 tropism for vascular endothelial cells.…”
Section: Endothelial Dysfunction In Covid-19mentioning
confidence: 99%
“…Importantly, the presence of fragmented SARS-CoV-2 viral genome or proteins in platelets and endothelial cells, but possibly also other cell types involved in thrombosis and hemostasis, suggests that these cells also are direct targets of the virus and that the resulting cellular activation, dysfunction and death contributes to thrombosis in COVID-19 [214][215][216][217]. As in other forms of cellular activation, the release of procoagulant EVs also may play a significant role in the micro-and macrovascular thrombotic complications associated with COVID-19.…”
Section: Extracellular Vesicles and Thrombosis Associated With Covid-19 Infectionmentioning
confidence: 99%
“…Other histologic examinations of post-mortem lungs failed to show evidence of endothelial cell infection [72], and a pre-print study showed that aortic, microvascular, and blood outgrowth endothelial cells are resistant to in vitro infection with SARS-CoV-2 [73]. Strong evidence of infection and virus production in the endothelium of mice and non-human primates infected with SARS-CoV-2 have been recently obtained [74].…”
Section: Focus On Direct Endothelium Infection By Sars-cov-2mentioning
confidence: 99%